Faktor-faktor yang mempengaruhi Integritas Laporan Keuangan (Studi Pada Perusahaan BUMN yang Terdaftar di BEI Periode 2020- 2022) - Novius, Andri (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
The aim of this research is to determine the influence of managerial ownership, audit committee, audit quality and company size on the integrity of financial reports. The objects in the research are state-owned companies registered on the IDX for the 2020-2022 period, totaling 20 companies. The sampling technique uses purposive sampling. Data analysis uses multiple linear regression. The research results explain that simultaneously managerial ownership, audit committee, audit quality and company size have a significant influence on the integrity of financial reports. While managerial ownership and company size have a negative and significant influence, the audit committee has a positive and significant influence, audit quality has a positive and insignificant influence.